Characterization of forsterite bioceramics - Sara Lee K.Y.; Christopher Chin K.M.; Ramesh S.; Tan C.Y.; Teng W.D.; Sopyan I. (2023)
The present work is on the synthesis of forsterite (Mg2SiO4) powder using talc and magnesium oxide powders as the starting materials followed by a heat treatment process. Sintering behavior and mechanical properties of the forsterite bodies were evaluated from 1200oC to 1500C. Forsterite phase were detected in samples without any secondary phases at all sintering temperatures. A very high fracture toughness of 4.9MPa.m1/2 and Vickers hardness of 7.1GPa were measured for samples sintered at 1400C, thus indicating the viability of this ceramic for biomedical application. (2012) Trans Tech Publications, Switzerland.